A Clot‐Homing Near‐Infrared Probe for In Vivo Imaging of Murine Thromboembolic Models. Issue 8 (18th January 2022) - Chen, Dan; Liu, Peiwen; Liu, Yurong; Wang, Zhiyou; Zhou, Yang; Jiang, Longguang; Yuan, Cai; Li, Yongkun; Lin, Wei; Huang, Mingdong
Abstract: Direct thrombus imaging contributes to early detection of thrombosis, and animal models with clinical relevance are vital in the development of new thrombolytics. Here, a facile clot‐homing strategy is developed based on the finding that blood clot is negatively charged. Positively charged pentalysine moiety is coupled with phthalocyanine‐based fluorophore, and its applications in murine thromboembolic models are described. The probe efficiently stains the cryosection of intracranial thrombi retrieved from patients with cardioembolic stroke. In vitro, the fibrin‐rich clot is labeled by the probe at sub‐nanomolar concentration. The probe‐labeled clot is formed into microparticles (1–5 µm) and intravenously injected into mice for pulmonary embolism modeling. In vivo imaging demonstrates fast accumulation and retention of fluorescent clot microparticles in pulmonary vessels. Recombinant tissue‐type plasminogen activator (rtPA) administration greatly reduces near‐infrared signal in the lungs in a time‐dependent manner. This probe is also tested in a stroke model. Middle cerebral artery is occluded by autologous thrombi formed under electric stimulation. In vivo imaging shows that the probe efficiently homes to thrombus at early stage. Hence, this probe has great potential in real‐time imaging of thromboembolism in clinically relevant models, promoting bench‐to‐bedside translation. This clot‐homing principle can be used in other applications. Abstract : Blood clot, composed of condense fibrin network, platelets, and red blood cells, carries many negative charges. A near‐infrared fluorophore (ZnPc5K, 680 nm) with positively charged pentalysine moiety can efficiently bind to blood clot, enabling in vivo 3D and real‐time imaging of thromboembolic disorders, e.g., pulmonary embolism and ischemic stroke.